TI_GERICHTE 12.2005.150 vom 23. November 2006 , Promessa di donazione immobiliare - nullità per vizio di forma - abuso di diritto - TI Tribunale d'appello (2006)
Promessa di donazione immobiliare - nullità per vizio di forma - abuso di diritto